1992
DOI: 10.1136/gut.33.6.807
|View full text |Cite
|
Sign up to set email alerts
|

Utility of a combined test of anorectal manometry, electromyography, and sensation in determining the mechanism of 'idiopathic' faecal incontinence.

Abstract: Combined tests of anorectal manometry, sphincter electromyography and rectal sensation were carried out in 302 patients with faecal incontinence (235 women, 67 men). The results obtained were compared with 65 normal subjects (35 women, 30 men). A mechanism for incontinence was identified in all and the majority of patients had more than one abnormality. Two hundred and seventy eight patients (92%) had a weak external anal sphincter, 185 of these (67%, mostly women) also showed abnormal perineal descent, and 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(101 citation statements)
references
References 23 publications
6
93
1
1
Order By: Relevance
“…Thus, the cause of fecal incontinence is often multifactorial (23)(24)(25). In a prospective study, 80% of patients had more than one pathogenic abnormality (23).…”
Section: Pathogenic Mechanisms and Etiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the cause of fecal incontinence is often multifactorial (23)(24)(25). In a prospective study, 80% of patients had more than one pathogenic abnormality (23).…”
Section: Pathogenic Mechanisms and Etiologymentioning
confidence: 99%
“…The duration of the sustained squeeze pressure provides an index of sphincter muscle fatigue. The ability of the external anal sphincter to contract in a reflex manner can also be assessed during abrupt increases of intraabdominal pressure such as when coughing (25,63,68,69). This reflex response causes the anal sphincter pressure to rise above that of the rectal pressure to preserve continence.…”
Section: Anorectal Manometry and Sensory Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…Fecal incontinence is regarded as a multifactorial condition as it is not usually associated with just one pathogenic abnormality. 17 Evaluation of the health impact is a clinical challenge, as proper assessment of patients needs to take into account the pathophysiology, pathogenesis, clinical severity, and quality of life (QoL) dimensions. Pathophysiological evaluation aims to determine the functional and structural elements implicated in fecal incontinence.…”
Section: Introductionmentioning
confidence: 99%
“…14 Evaluation of rectal sensory function in patients with UFI has demonstrated that up to ,50% of patients have evidence of rectal hypersensitivity (RH) to simple volumetric balloon distension-that is, reduced sensory thresholds. 5 15 We have recently shown that in patients with UFI, RH is associated with increased bowel frequency, reduced ability to defer defecation, increased pad usage, and negative lifestyle effects. 5 Motor function of the colon and rectum is an integrated process involving myoelectrical and contractile activity, tone, compliance, wall tension, and stool transit.…”
mentioning
confidence: 99%